Influence of Survivors’ Entrapment Factors and Traffickers’ Characteristics on Perceptions of Interpersonal Social Power While Being Recruited To Be Trafficked - Preble, Kathleen M. (Violence against women, 2021)
Although scholarship about human trafficking has grown in the last two decades, not much is understood about interpersonal dynamics in human trafficking experiences. This article explores human trafficking victims’ (n = 31, female, international) perceptions of traffickers’ interpersonal social power during the recruitment phase of the trafficking experience. Findings from this study revealed that entrapment factors and shared common characteristics between victim and trafficker prior to trafficking did little to influence perceptions of interpersonal social power among victims. Understanding victims’ perceptions of interpersonal social power is critical to developing targeted prevention and intervention services for women at risk for becoming trafficked.